Mental Health Awareness: Breaking the Stigma - Akram, Muhammad; Abbas, Sabahat; Umaru, Isaac John (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2025)
Mental health remains a vital component of an individual’s overall health which is often stigmatized and prevents people from receiving the help they need. The stigma is perpetuated through deeply ingrained misunderstandings, social alienation, and systemic obstacles that make it necessary to focus on the promotion of education, advocacy, and reforms. Education helps achieve the difficult task of addressing stereotypes and promoting empathy and normalization of mental health awareness advocates in for enhanced access to care, funding, and policy support. Initiatives by the community and responsible media portrayals aid in changing perceptions in the public which helps people seek the help they need without being judged. Thus, the more the stigma is conquered concerning mental health the more positive and supportive environment is created which helps in improving the society’s overall mental health and life quality.